Clinicopathologic Characteristics of Gastroenteropancreatic Neuroendocrine Tumors: Experience of a National Referral Hospital in Indonesia - Stephanie, Marini; Rahadiani, Nur; Maulahela, Hasan; Syaiful, Ridho Ardhi; Handjari, Diah Rini; Krisnuhoni, Ening (Open Access Macedonian Journal of Medical Sciences, 2022)
Gastroenteropancreatic neuroendocrine tumors (GEP-NETs) have variable biological behavior although they are all malignant. This study presents the 10-year prevalence along with the clinicopathologic characteristics of GEP-NETs and their association with tumor grade at a national referral hospital in Indonesia. This is a retrospective cross-sectional study of patients with GEP-NET confirmed by histomorphology and immunohistochemistry who presented to Cipto Mangunkusumo Hospital from 2009 to 2019. Clinical characteristics included age, sex, primary site, tumor stage, metastasis, hormone status, and chief complaints. Pathological characteristics included the type of GEP-NET, specimen type, grade, and presence of lymphovascular invasion (LVI). Statistical analysis was performed to determine the association between characteristics and tumor grade. A total of 84 cases of GEP-NET from 2009 to 2019 were included; of these, 38.1% were neuroendocrine tumors (NETs), 28.6% were neuroendocrine carcinomas (NECs), and 33.3% were mixed neuroendocrine-non-neuroendocrine neoplasm (MiNEN). The mean patient age was 48.36 years, and the male to female ratio was 1. GEP-NETs predominantly originated from the rectum (21.4%) and were mostly non-functioning (90.5%) with an average tumor size of 4.77 cm. Most tumors were localized (53.6%), but metastasis was found in 28.6% cases. LVI was positive in 35.7% cases. High-grade tumors were more common (54.3%) than low-grade tumors. High-grade tumors were associated with unknown primary sites, dissemination, LVI, and larger tumor size. To conclude, GEP-NETs can arise from any site in the gastrointestinal tract and have variable clinicopathologic characteristics. Primary site, stage, LVI, and tumor size are associated with grade.